IMPLEMENTASI SIX SIGMA MENGGUNAKAN NEW SEVEN TOOLS PADA PERBAIKAN KUALITAS AMPLANG DI UD KELOMPOK MELATI - Raden Rizki Amalia; Nina Hairiyah; Nuryati Nuryati (AGROINTEK, 2023)
UD Melati Group is a home industry for processing amplang. In the production process, non-standard products were found. This study aims to improve the quality of amplang products by identifying the types and causes of amplang defects, compiling corrective steps and implementing the repair phase. The method used is to apply six sigma using the new seven tools. Data collection is done by direct observation in the field, interviews, and literature studies. The results showed that the types of defects found in the Melati Group UD were non-swelling amplang and hollow amplang with an average sigma value of 1.9831 and a DPMO of 314,500, which means that each production process with the possibility of damage is 314,500 seeds for one million amplang seeds produced. . The main factors causing defects are dough that is too thick, forgetting to add soda, not stirring continuously during frying, stirring and mixing fish, flour and spices that are not smooth, grinding fish that is not soft, fish that are too big/old , and fish that are too small. After the repair, the sigma value increased from 1.98 to 2.3414 and the DPMO value decreased by 11.45% from 314,500 seeds to 200,000 seeds.